2016
DOI: 10.1016/j.algal.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficient targeting of recombinant proteins to the thylakoid lumen in Chlamydomonas reinhardtii using a bacterial Tat signal peptide

Abstract: 19Interest in the exploitation of microalgae for biotechnological applications has 20 increased over the last decade, and microalgae are now viewed as offering a 21 sustainable alternative to traditionally used host chassis. A number of recombinant 22proteins have been expressed in genetically modified algal strains, with the green alga 23Chlamydomonas reinhardtii being a particularly popular host strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…In most cases these are single subunit proteins and therefore involve the introduction of only a single transgene, although there have been a few examples of multigenic engineering of the plastome [32,33]. To date, all of the therapeutic proteins that have been reported are soluble and accumulate in the chloroplast stroma, save for a single report of the targeting of an antibody fragment to the thylakoid lumen [34], although membrane-anchored proteins have been successfully produced in the algal chloroplast [35].…”
Section: Biopharmaceuticals Made In the C Reinhardtii Chloroplastmentioning
confidence: 99%
“…In most cases these are single subunit proteins and therefore involve the introduction of only a single transgene, although there have been a few examples of multigenic engineering of the plastome [32,33]. To date, all of the therapeutic proteins that have been reported are soluble and accumulate in the chloroplast stroma, save for a single report of the targeting of an antibody fragment to the thylakoid lumen [34], although membrane-anchored proteins have been successfully produced in the algal chloroplast [35].…”
Section: Biopharmaceuticals Made In the C Reinhardtii Chloroplastmentioning
confidence: 99%
“…To investigate the impact on growth of dsRNA expression in the PYP strain, the growth of the strain was analyzed in comparison to a previously generated transformant that has the pSRSapI vector integrated in its chloroplast genome without a gene of interest (strain termed SR) 15 . This strain was chosen as a control since the TN72 strain used for transformation cannot grow phototrophically.…”
Section: Resultsmentioning
confidence: 99%
“…The growth of the generated C. reinhardtii strain expressing dsRNA-YHV (PYP) was analyzed in direct comparison to a control strain (TN72 transformed with the pSRSapI plasmid) previously generated 15 . Pre-cultures of both strains were prepared as described in Section 2.1 and 10 mL of each strain were re-inoculated into 400 mL TAP medium with continuous shaking at 100 rpm and 50 µmol photons m −2 s −1 illumination at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The authors demonstrated the usefulness of synthetic promoters to drive gene expression as a complementary method for the production of recombinant proteins. With another method, bacterial Tat export signal peptides were applied to translocate recombinant proteins within the thylakoid lumen of the C. reinhardtii chloroplast, and the result presented an innovative approach of using thylakoid lumen as a new compartment for producing recombinant proteins, which provided more protective environments for delicate proteins [ 30 ].…”
Section: Emerging Trends In Genetic Engineering Of Microalgae For Com...mentioning
confidence: 99%